Politics of Subsidiarity in Refugee Reception: The Case of Civil Society in Turkey - Bosnak, Buke (Routledge Journals, Taylor & Francis Ltd, 2021)
This article examines responses and strategies of civil society in Turkey to reception policies in the context of the Syrian forced migration. Based on interviews with public officials and representatives from humanitarian and right-based organizations, I show that strategies of civil society are shaped by institutional, discursive, and international opportunity structures. On the one hand, humanitarian organizations build alliances with the state and employ religious frames and venue shopping to legitimize state policies on refugees. On the other hand, rights-based organizations conduct advocacy and formed alliances with the media, utilizing frames of rights and justice and venue shopping at the European level.
Keywords: Civil Society; Political Opportunity Structures; Alliance Formation; Framing; Venue Shopping; Syrian Refugees; Turkey; Eu; Syrian Refugees; Organizations; Representation; Opportunities; Migration; Policy